An innovative measure of orthographic processing: Development and initial validation. (July 2020) - Chen, Yi-Jui Iva; Wilson, Mark; Irey, Robin C.; Requa, Mary K.
Orthographic processing – the ability to perceive, access, differentiate, and manipulate orthographic knowledge – is essential when learning to recognize words. Despite its critical importance in literacy acquisition, the field lacks a tool to assess this essential cognitive ability. The goal of this study was to design a computer-based assessment of orthographic processing and investigate its psychometric properties. The rationale for designing specific items was discussed, methods used to separate orthographic processing from word recognition and spelling ability were presented, and item suitability was examined. Person separation reliability was .91 for this assessment. Validity evidence was gathered and reported.